Political Transition, Health System Reform and Trust in Childhood Vaccination in Ukraine: A Qualitative Case Study - Harriet Dwyer; Jennifer Palmer; Luisa Enria; Anton Grushetskyi; Olya Fokaf; Kateryna Gatsenko; Hanna Yahorava; Nadine Beckmann (The International Journal of Health Planning and Management, 2026)
ABSTRACT Trust in childhood vaccination is a concern for health policy, particularly in settings of political transition and conflict, where governance, institutional legitimacy and service delivery are often under strain. It is against this backdrop that this study aims to describe evolving interactions between health system governance, trust and childhood vaccination in Ukraine across periods of reform and conflict, and the implications for health policy in fragile settings. Drawing on qualitative interviews with key informants and Ukrainian parents, findings show that trust in the health system, with implications for vaccine confidence, has been intertwined with broader perceptions of the legitimacy of state institutions and quality of services. Trust was undermined by corruption and weak governance but reconfigured through reforms that increased accountability and patient choice. The 2022 full‐scale invasion disrupted services but also strengthened forms of civic responsibility and engagement with public health. This study contributes to broader scholarship on health system trust and vaccine confidence by situating them within the historical and political evolution of Ukraine. It offers considerations relevant for Ukraine's post‐conflict recovery and health governance and illustrates links between vaccine confidence and state‐society relations in contexts of political transition and crisis.